1969
DOI: 10.1111/j.1432-1033.1969.tb19644.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Degradation in Escherichia coli

Abstract: 1. An enzymatic activity is described in oleate-grown cells of E. coli, which has the cofactor requirements of a long chain acid : CoA ligase (AMP). This enzyme is a t least partially membrane bound and activates saturated and mono-and polyunsaturated fatty acids. It is inactive with butyrate and hexanoate. The enzyme is induced by oleate under similar conditions, but a t different relative rates, as three other enzymes of fatty acid degradation (thiolase, crotonase, hydroxyacylCoA dehydrogenase) which are und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…These results indicated that FadK could functionally replace FadD under anaerobic conditions. However, fadD mutants are unable to grow on long chain fatty acids aerobically (8,18,19) and thus the failure of FadK to replace FadD under aerobic conditions was attributed to insufficient expression of FadK or to impairment of enzyme function.…”
mentioning
confidence: 99%
“…These results indicated that FadK could functionally replace FadD under anaerobic conditions. However, fadD mutants are unable to grow on long chain fatty acids aerobically (8,18,19) and thus the failure of FadK to replace FadD under aerobic conditions was attributed to insufficient expression of FadK or to impairment of enzyme function.…”
mentioning
confidence: 99%
“…Addition of long chain (ϾC 12 ) fatty acids induces the fad enzymes, whereas medium (C 7 -C 11 ) or short chain-length (C 4 -C 6 ) fatty acids cannot (11,12). Therefore, wild-type E. coli strains utilize long-chain fatty acids such as oleate (C18:1), but not medium-chain-length fatty acids such as decanoate (C10:0) as sole carbon and energy sources.…”
mentioning
confidence: 99%
“…Therefore, wild-type E. coli strains utilize long-chain fatty acids such as oleate (C18:1), but not medium-chain-length fatty acids such as decanoate (C10:0) as sole carbon and energy sources. However, mutants that grow on decanoate are readily isolated by plating wild-type cells onto minimal media containing this acid as sole carbon source (11,12). These stains have constitutive levels of the fad enzymes and have mutations that map in fadR (2,11,13).…”
mentioning
confidence: 99%
“…Next, we examined whether or not AcsA complements the FadD (longchain acyl CoA synthetase)-deficient strain (K27). In contrast Overall Nitrile Pathway Involving Acyl-CoA Synthetaseto the wild-type strain that grew in the medium containing a long-chain fatty acid (oleate) as the sole carbon and energy source, the K27 strain did not grow (38,43). We transformed the K27 strain with pUC-acsA and plated the transformants on glucose or oleate minimal agar plates, respectively.…”
Section: Cloning and Nucleotide Sequence Of The 3ј Downstreammentioning
confidence: 99%
“…E. coli BL21-CodonPlus(DE3)-RIL (Novagen, Madison, WI) was used as the host for one plasmid, pET-24a(ϩ) (Novagen), and its derivative, and it was also used for expression of the acyl-CoA synthetase gene (acsA). E. coli acetyl-CoA synthetase-deficient mutant strain AJW1781 (CGSC#8076; ⌬acs-1::kan thr-1 leuB6(Am) ⌬(codB-lacI)3 rpsL136 metF159(Am) thi-1) (37) and long-chain acyl-CoA synthetase-deficient mutant strain K27 (CGSC#5478; fadD88) (38) DNA Manipulations-Restriction endonucleases, DNA polymerase, and T4 DNA ligase were purchased from Toyobo Co., Ltd. (Osaka, Japan). Nucleotides were sequenced by the dideoxy-chain terminating method using an ABI Prism 310 genetic analyzer (Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%